2020
DOI: 10.14814/phy2.14592
|View full text |Cite
|
Sign up to set email alerts
|

Activation of multiple receptors stimulates extracellular vesicle release from trophoblast cells

Abstract: Reports of the stimulated release of extracellular vesicles (EVs) are few, and the mechanisms incompletely understood. To our knowledge, the possibility that the activation of any one of the multitudes of G‐protein‐coupled receptors (GPCRs) expressed by a single cell‐type might increase EV release has not been explored. Recently, we identified the expression of cholecystokinin (CCK), gastrin, gastrin/cholecystokinin types A and/or B receptors (CCKAR and/or –BR), and the bitter taste receptor, TAS2R14 in the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Activation of CCKBR, TAS2R14, cholinergic muscarinic 1 and 3, and angiotensin II receptors, each increased EV release without affecting the overall size of the EVs [17]. Also, EV release by the calcium ionophore, A23187, was less robust when compared to receptor-mediated stimulation [17]. These finding warrant the investigation on whether activation of other GPCRs can mediate EV release.…”
Section: Ev Release In Health and Diseasementioning
confidence: 93%
See 2 more Smart Citations
“…Activation of CCKBR, TAS2R14, cholinergic muscarinic 1 and 3, and angiotensin II receptors, each increased EV release without affecting the overall size of the EVs [17]. Also, EV release by the calcium ionophore, A23187, was less robust when compared to receptor-mediated stimulation [17]. These finding warrant the investigation on whether activation of other GPCRs can mediate EV release.…”
Section: Ev Release In Health and Diseasementioning
confidence: 93%
“…The size of EVs may or may not depend on the amount and type of cargo enriched in the vesicles. Some studies have shown an increase in EV release without a change in EV size, while other studies have shown the contrary [17,18]. Apoptotic bodies represent the largest type of EVs and contain organelles, in addition to nucleic acids, proteins, and lipids.…”
Section: Regulation Of Size Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, EX release from cells in response to DNA damage is under the control of p53-driven gene expression, and EX-derived miRNA are essential for mutant p53-associated oncogenesis (49). Furthermore, the stimulation of cholecystokinin receptors (CCKR) have been shown to increase the release of EVs by more than 2-fold in human and mouse trophoblast cell lines (50). The increased presence of proteins associated with these pathways in EX-enriched samples suggests that it is possible to isolate these EX-populations in peripheral blood plasma, which could be of utility in clinical studies.…”
Section: Ex-associated Pathways Display Variable Enrichment Dependent Upon Ex Isolation Methodmentioning
confidence: 99%
“…As mentioned earlier, if the predominant role of EVs is to impede viral infection, then increasing the release of EVs may prove beneficial. Although stimulated release of EVs has not been extensively and systematically investigated (Alonso et al., 2005; Pironti et al., 2015; Verweij et al., 2018), activation of several G‐protein‐coupled receptors (GPCRs) was recently found to increase EV release from a single cell type (trophoblast‐derived cells) (Conrad et al., 2020). It was speculated that, because there are as many as 800 GPCRs in the human genome, many of which can be expressed by one given cell‐type (Kroeze et al., 2003), perhaps each GPCR (or cohort of functionally related GPCRs) can affect EV release in a cell‐type‐specific manner containing a unique subset of cargo (e.g., RNAs, proteins, lipids) that, in turn, coordinates specific physiological responses among neighboring and distant cells (Conrad et al., 2020).…”
Section: Rationalementioning
confidence: 99%